Processos de separação por membranas para reciclo de águas do processo de extração e purificação de ficocianina - Gamba, Verônica (2022)
Spirulina sp. is a species of microalgae that contains in its phycobiliproteins phycocyanin, a blue pigment with therapeutic properties and high protein nutritional value. Its application has been expanded as a result of FDA approval as the first natural dye to be used in the food industry. However, the processes for obtaining phycocyanin require high consumption of water. The extraction by phosphate buffer and the concentration and purification through membrane separation, when compared to chromatographic and chemical methods, has a simpler operation and ease in it industrial scale. The objective of this work is to verify the possibility of reusing the buffer-phosphate extraction solution with reverse osmosis from the phycocyanin extraction and purification process. The extraction and concentration was carried out through an ultrafiltration membrane, with a pressure of 1.5 bar and a concentration of 50% of the initial volume of phycocyanin. Purification was carried out through the diafiltration method, feeding ultrapure water in a proportion of three times the volume that was desired to be purified. To recover the permeates from this process, a reverse osmosis membrane was used, where the following operating conditions were evaluated: pressure of 1, 2 and 3 bar for the diafiltration water; and pressure of 4, 5 and 6 bar for the permeate from the concentration. As a response factor and statistical analysis, the following parameters were evaluated: phosphate concentration, permeate flux and conductivity. After analyzing the water balance of the process, the feasibility of the proposed method would be more effective when there is a mixture of permeates. Therefore, the second test was performed evaluating the pressure of 3, 4 and 5 bar and the concentration factors of 50% and 75%. The best recovery condition was at a pressure of 5 bar and a concentration of 75%, with a flow reduction from 160 L.m-².h-1 to 59 L.m-².h-1. Through this condition, it was possible to obtain a reverse osmosis permeate with characteristics of ultrapure water, free of phosphate and phycocyanin, and its reuse in diafiltration is promising. The waste from the process presented a concentration of 5620 mg.L-1 of phosphate, representing an increase of 75% in the initial concentration of the original phosphate solution. The re-extraction using reverse osmosis waste showed promising characteristics, as there was an increase of 30% in the concentration of phycocyanin and 35% in its purity, when compared to the traditional method of extraction. The membrane separation processes were efficient in the recovery of residues from the extraction and purification of phycocyanin. This process makes it possible to reduce the volume of water used in the process by 80% compared to the traditional process.